2001
DOI: 10.1111/1467-8624.00273
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Efficacy Beliefs as Shapers of Children's Aspirations and Career Trajectories

Abstract: This prospective study tested with 272 children a structural model of the network of sociocognitive influences that shape children's career aspirations and trajectories. Familial socioeconomic status is linked to children's career trajectories only indirectly through its effects on parents' perceived efficacy and academic aspirations. The impact of parental self-efficacy and aspirations on their children's perceived career efficacy and choice is, in turn, entirely mediated through the children's perceived effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
1,127
2
74

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,451 publications
(1,299 citation statements)
references
References 94 publications
37
1,127
2
74
Order By: Relevance
“…One domain where Bandura and colleagues demonstrated the potency of self-efficacy is child development (e.g., Bandura et al, 2001;Pastorelli et al, 2001). Bandura and colleagues (2001) used a longitudinal design featuring a two-cohort structure to assess cognitive mechanisms impacting children's career plans.…”
Section: Self-efficacy: Theory and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…One domain where Bandura and colleagues demonstrated the potency of self-efficacy is child development (e.g., Bandura et al, 2001;Pastorelli et al, 2001). Bandura and colleagues (2001) used a longitudinal design featuring a two-cohort structure to assess cognitive mechanisms impacting children's career plans.…”
Section: Self-efficacy: Theory and Applicationmentioning
confidence: 99%
“…Various types of self-reported self-efficacy have proven to follow this assertion. Areas where this has held true include academic (e.g., Bandura et al, 2001;Pastorelli et al, 2001), business (e.g., Judge et al, 2007;Stajkovic & Luthans, 1998), and self-defense training (e.g., Ozer & Bandura, 1990) situations to name a few. Witness testimony does not follow suit; therefore, SET does not function as expected in the courtroom setting.…”
Section: Clarifying Self-efficacy Theory In a Legal Contextmentioning
confidence: 99%
“…De facto, e de acordo com a literatura, as motivações escolares têm perfi s distintos em cada um dos géneros podendo estar relacionadas com os estereótipos de género sobre os interesses por diferentes matérias escolares (Anderman & Young, 1994;Bandura et al, 2001;Meece & Painter, 2008;Middleton & Migdley, 1997;Zimmerman & Martinez-Pons, 1990). Ao contrário do que se verifi ca em outros estudos (Bandura et al, 2001;Pajares & Valiante, 2001;Schunk & Pajares, 2005), não se encontraram diferenças de género nas expectativas de autoefi cácia. Isto signifi ca que rapazes e raparigas não diferem, de modo signifi cativo, nas expectativas que têm sobre a capacidade de autorregular o seu comportamento e ter sucesso na realização das tarefas escolares.…”
Section: Discussionunclassified
“…A investigação prova que as diferenças de género nas expectativas de autoefi cácia estão também relacionadas com a idade ou ano escolar (Schunk & Pajares, 2005). Estas diferenças começam a acentuar-se nos anos escolares correspondentes à puberdade e adolescência e parecem estar associadas a uma preocupação crescente com a adequação aos estereótipos de género (Bandura, Barbaranelli, Caprara, & Pastorelli, 2001).…”
unclassified
“…Researches carried out in the field of self-efficacy by Bandura et al (2001) have indicated that, the more the pupils perceive themselves as having a higher level of selfefficacy, the more they will persevere in obtaining good scholastic results. At the same time, they will have a lower risk of school dropout (Quiroga, Janosz, Bisset and Morin, 2013 apud Gherasim and Butnaru, 2013).…”
Section: Open Volume 9 Number 12 Year 2016mentioning
confidence: 99%